Forget "militarization": race, disability and the "martial politics" of the police and of the university. Issue 2 (3rd April 2018) - Howell, Alison
ABSTRACT: This article investigates the limits of the concept of militarization and proposes an alternative concept: martial politics. It argues that the concept of militarization falsely presumes a peaceful liberal order that is encroached on by military values or institutions. Arguing instead that we must grapple with the ways in which war and politics are mutually shaped, the article proposes the concept of martial politics as a means for examining how politics is shot-through with war-like relations. It argues that stark distinctions cannot be made between war and peace, military and civilian or national and social security. This argument is made in relation to two empirical sites: the police and the university. Arguing against the notion that either the police or the university have been "militarized, " the article provides a historical analysis of the ways in which these institutions have always already been implicated in martial politics – that is, of producing White social and economic order through war-like relations with Indigenous, racialized, disabled, poor and other communities. It concludes by assessing the political and scholarly opportunities that are opened up for feminists through the rejection of the concept of militarization in favor of the concept of martial politics.